Reimagining India's urban future: A framework for securing high-growth, low-carbon, climate-resilient urban development in India - Meenu Tewar; Zeba Aziz; Mitchell Cook; Amrita Goldar; Indro Ray; Saon Ray; Sahana Roy Chowdhury; Vidhya Unnikrishnan (Indian Council for Research on International Economic Relations (ICRIER), 2015)
India is at the cusp of a major urban transition. In less than twenty years, India's urban population is expected to nearly double from 377 million today to over 600 million. Indian cities already contribute an estimated two-thirds of India's GDP, and this number is expected to rise to 75% by 2031. With 70% of all new jobs expected to come from urban areas, accommodating a growing urban workforce will require large investments in new urban spaces. How prepared is India to deal with this rapid, inevitable urban expansion? The evidence on the ground suggests that the costs of India's current pattern of urbanization are unsustainably high. Deep existing deficits in basic urban services such as housing, transit, water, sanitation and energy have led to a plethora of urban woes. These range from the economic, institutional and carbon costs of managing unplanned growth, congestion, poor quality of life, burgeoning slums and pollution levels that have come to threaten basic public health. [...]
Keywords: R1; R11; R12; 330; economic growth; urbanization; urban growth; spatial development; land use patterns; carbon emissions; urban infrastructure; mitigation options; adaptation; sustainable and inclusive growth; accessibility; urban resilience; municipal finance